Suppression of non-prompt J/ψ, prompt J/ψ, and Y(1S) in PbPb collisions at √s NN = 2.76 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
Yields of prompt and non-prompt J/ψ, as well as Y(1S) mesons, are measured by the CMS experiment via their μ +μ - decays in PbPb and pp collisions at √/s NN = 2.76 TeV for quarkonium rapidity |y| < 2.4. Differential cross sections and nuclear modification factors are reported as functions of y and transverse momentum pT, as well as collision centrality. For prompt J/ψ with relatively high pT (6.5 < pT < 30 GeV/c), a strong, centrality-dependent suppression is observed in PbPb collisions, compared to the yield in pp collisions scaled by the number of inelastic nucleon-nucleon collisions. In the same kinematic range, a suppression of non-prompt J/ψ, which is sensitive to the in-medium b-quark energy loss, is measured for the first time. Also the low-pT Y(1S) mesons are suppressed in PbPb collisions. © CERN.